Bone histology of Iberosuchus macrodon (Sebecosuchia, Crocodylomorpha). (27th March 2017) - Cubo, Jorge; Köhler, Meike; de Buffrénil, Vivian
Abstract : Iberosuchus macrodon is a Cenozoic crocodyliform interpreted as a terrestrial, cursorial form. To assess whether this adaptation was accompanied by a high growth rate and an elevated resting metabolic rate (two features commonly attributed to several terrestrial Triassic Crocodylomorpha based on histology), we studied bone histology in the femora of two specimens attributed to I. macrodon . Beyond this question is the broader problem of the possible survival to the Cretaceous‐Palaeogene extinction event of tachymetabolic sauropsids other than birds. At mid‐diaphysis, bone cortices in Iberosuchus are made of a parallel‐fibred tissue that turns locally to true lamellar bone. Cortical vascularization consists of simple longitudinal canals forming a network of medium density. The spacing pattern of conspicuous lines of arrested growth suggests asymptotic growth for Iberosuchus . This general histological structure prevails also in the metaphyseal region of the bones. It is basically similar to that encountered in certain large lizards adapted to active predation, the Varanidae and the Teidae. In one of the two Iberosuchus femora, however, an intracortical meniscus made of a tissue displaying a global radial architecture occurs in the region of the fourth trochanter. Histologically, the latter can be interpreted either as compacted spongiosa or as a fibro‐lamellar complex with a gross radial orientation, a tissue corresponding to fast periosteal apposition. These observations suggest that Iberosuchus basically had a slow, cyclical growth indicative of an ecto‐poikilothermic, lizard‐like, resting metabolic rate. However, it might also have retained a limited capacity for fast periosteal accretion in relation to local morphogenetic requirements as, for instance, the development of crests or trochanters.